1997
DOI: 10.1016/s0012-9593(97)89925-9
|View full text |Cite
|
Sign up to set email alerts
|

The hilbert schemes of degree three curves

Abstract: In this paper we show that the Hilbert scheme H(3, g) of locally Cohen-Macaulay curves in P 3 of degree three and genus g is connected. This is achieved by giving a classification of these curves, determining the irreducible components of H(3, g), and giving certain specializations to show connectedness. As a byproduct, we find that there are curves which lie in the closure of each irreducible component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 9 publications
0
54
0
7
Order By: Relevance
“…Suppose that X is not contained in any quartic surface. If X is ACM, then X is linked to a line, otherwise X is linked to double lines of genus −1 by the following successive linkages: ACM X The Hilbert schemes H 2 g of double lines of genus g ≤ 0 were studied by Migliore (1986) and Nollet (1997). In the studies, the Hilbert scheme H 2 −1 was shown to be irreducible and of dimension 8.…”
Section: Nasumentioning
confidence: 99%
“…Suppose that X is not contained in any quartic surface. If X is ACM, then X is linked to a line, otherwise X is linked to double lines of genus −1 by the following successive linkages: ACM X The Hilbert schemes H 2 g of double lines of genus g ≤ 0 were studied by Migliore (1986) and Nollet (1997). In the studies, the Hilbert scheme H 2 −1 was shown to be irreducible and of dimension 8.…”
Section: Nasumentioning
confidence: 99%
“…The results about closures also involve standard methods but are more subtle: for example to identify F sp with F 2 ∩F 3 we rely on previous work on the closure of the family of rational normal curves, such as [24,29,30,32].…”
Section: Nets Of Quadricsmentioning
confidence: 99%
“…by Hartshorne [5], Bǎnicǎ and Manolache [3] and Manolache [7], [10]. One should also mention that the Hilbert scheme of (locally) Cohen-Macaulay curves in P 3 is connected for degree 3 (Nollet [15]) and degree 4 (Nollet and Schlesinger [16]). …”
Section: Introductionmentioning
confidence: 99%